2011
DOI: 10.1007/dcr.0b013e3181fcee68
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carcinoembryonic Antigen After Neoadjuvant Chemoradiotherapy in Patients With Rectal Cancer

Abstract: Combined pre- and postchemoradiotherapy CEA levels could be useful as a prognostic factor for disease-free survival in patients with rectal cancer who undergo treatment with neoadjuvant chemoradiotherapy and curative resection. Postchemoradiotherapy CEA may be helpful in a selection of patients who want more conservative surgery after chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 35 publications
1
43
1
5
Order By: Relevance
“…However, not only the pre-CRT CEA level but also the post-CRT CEA level, and/or the change in the CEA pattern after CRT, are often analyzed together. The latter two measures are more closely related to the pathological CRT response than is the pre-CRT CEA level [58][59][60]. This is not surprising because the latter values reflect the degree of CRT response.…”
Section: Predictive Markers Clinicopathological Factorsmentioning
confidence: 91%
“…However, not only the pre-CRT CEA level but also the post-CRT CEA level, and/or the change in the CEA pattern after CRT, are often analyzed together. The latter two measures are more closely related to the pathological CRT response than is the pre-CRT CEA level [58][59][60]. This is not surprising because the latter values reflect the degree of CRT response.…”
Section: Predictive Markers Clinicopathological Factorsmentioning
confidence: 91%
“…Perez et al reported that a CEA-post level < 5 ng/mL was associated with increased rates of clinical CR and pCR (37). CEA-post with a different cut-off value of 2.7 ng/mL was also proved to be an independent predictor of good tumor regression (p = 0.001) (38). In a recent study, CEA-post < 2.61 ng/mL also showed a strong predictive value for pCR with a sensitivity of 76.0% and specificity of 58.4% in patients with a low CEA-pre level or in patients with a high CEA-pre level but normalized CEA-post levels (39).…”
Section: Serum Carcinoembryonic Antigen (Cea)mentioning
confidence: 99%
“…There is controversy if CEA-pre could be a predictive marker for pCR or not (34)(35)(36)(37)(38)(39). CEA change groups were relevant to pCR, but may not be significant enough (37,38).…”
Section: Serum Carcinoembryonic Antigen (Cea)mentioning
confidence: 99%
See 1 more Smart Citation
“…Different cutoff level for CEA was found to be significant for prediction of pCR in several studies. Most studies proposed 5 ng/ml [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and others 2.5 ng/ml [9,28], 3 ng/ml [29,30], 3.5 ng/ml [31,32] or 6 ng/ml [22]. Therefore, elevated CEA level was defined as ≥ 5 ng/ml, and normal CEA level refers to <5 ng/ml in current study.…”
Section: Data Extraction and Definitionsmentioning
confidence: 99%